SAT0115 Tofacitinib Versus Biologic Treatments in Patients with Active Rheumatoid Arthritis Who have had an Inadequate Response to Tumour Necrosis Factor Inhibitors - A Network Meta-Analysis. (23rd January 2014) - Vieira, M. C.; Wallenstein, G.; Bradley, J.; Gruben, D.; Koncz, T.; Zwillich, S. H.; Jansen, J. P.
Abstract : Background: Tofacitinib is a novel, oral Janus kinase (JAK) inhibitor for the treatment of rheumatoid arthritis (RA). Objectives: To compare the efficacy and safety of tofacitinib 5 mg and 10 mg twice daily (BID) relative to biologic disease-modifying antirheumatic drugs (DMARDs) in the treatment of RA patients with a prior inadequate response to tumour necrosis factor inhibitors (TNFi-IR). Methods: Five randomised controlled trials (RCTs) evaluating tofacitinib combined with methotrexate (MTX) and various biologic DMARDs combined with non-biologic DMARDs, were identified through a systematic literature search. 1 -9 Individual study efficacy data, based on American College of Rheumatology (ACR) responses and change from baseline in Health Assessment Questionnaire (HAQ) at Week 12, were combined with network meta-analyses. Comparisons of safety were based on rates of treatment withdrawal due to adverse events (AEs). Results: The RCT arms of interest included 1946 patients: mean ages 52.2–55.4 years; mean disease duration 9.6–12.6 years; mean swollen and tender joint counts 14–23.4 and 26–33.9, respectively. Tofacitinib 5 mg and 10 mg BID combined with MTX showed relative risk estimates of ACR responses comparable to abatacept, golimumab, rituximab and tocilizumab combined with nonbiologic DMARDs at Week 12 (Table). Based on HAQ scores, tofacitinib was more efficacious than golimumab, and comparable with rituximab. Withdrawal rates from trials due to AEs were comparable. Image/graph: Conclusions: Analyses of available RCTs revealed that tofacitinib has similar efficacy in improving signs and symptoms as biologic DMARDs for TNFi-IR patients. Further analyses are needed to explore factors that may impact the magnitude of the placebo response and factors that could confound comparative treatment effects in RA management (e.g. starting DMARD dose, duration and number of prior TNFi). Also, safety comparisons over a longer time period would be more informative. References: Westhovens R et al. Rheumatology 2006; 45: 1238–46; Genovese MC et al. N Engl J Med 2005; 353: 1114–23; Smolen JS et al. Lancet 2009; 374: 210–21; Emery P et al. Ann Rheum Dis 2008; 67: 1516–23; Keystone E et al. Arthritis Rheum 2008; 59: 785–93; Keystone E et al. Ann Rheum Dis 2009; 68: 216–21; Cohen SB et al. Arthritis Rheum 2006; 54: 2793–806; Cohen SB et al. Ann Rheum Dis 2010; 69: 1158–61; Burmester GR et al. Lancet 2013; Jan 4 [Epub ahead of print] Disclosure of Interest: M. Vieira Consultant for: Pfizer Inc., G. Wallenstein Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., J. Bradley Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., D. Gruben Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., T. Koncz Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., S. Zwillich Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., J. Jansen Consultant for: Pfizer Inc.